Advancements and prospects of boundary layer ingestion propulsion concepts - Moirou, Nicolas G. M.; Sanders, Drewan S.; Laskaridis, Panagiotis (Elsevier, 2023)
The aviation sector is experiencing an increasing pressure to reduce emissions via long-term strategies for a ceaselessly growing number of flight passengers. Aircraft currently in operation have typically been designed by considering the airframe somewhat separately from the propulsion system. In doing so, conventional aero-engine architectures are approaching their limits in terms of propulsive efficiency, with technological advancements yielding diminishing returns. A promising alternative architecture for improving the overall performance of the next generation of commercial aircraft relies upon boundary layer ingestion (BLI). This technology aerodynamically couples the airframe with a strategically positioned propulsion system to purposely ingest the airframe’s boundary layer flow. Nonetheless, there is a lack in consensus surrounding the interpretation and quantification of BLI benefits. This is primarily because conventional performance accounting methods breakdown in scenarios of strong aerodynamic coupling. Subsequently, there is a major challenge in defining appropriate performance metrics to provide a consistent measurement and comparison of the potential benefits. This review examines the various accounting methods and metrics that have been applied in evaluating BLI performance. These are discussed and critiqued in the context of both numerical and experimental models. Numerically, the geometric, aerodynamic and propulsive models are sorted by their orders of fidelity along with the plenitude of methods used for flow feature identification enabling a phenomenological understanding of BLI. Particular attention is then given to experimental BLI models with their different set-ups, methods and associated limitations and uncertainties. Finally, the numerous unconventional BLI aircraft concepts are categorised, compared and critiqued with reference to their associated design exploration and optimisation studies.
Keywords: Boundary layer ingestion; Conceptual aircraft; Distributed propulsion; Engine-airframe integration; Performance accounting; Propulsive fuselage